Peer review of the pesticide risk assessment of the active substance isoflucypram. (23rd June 2022) - ,; Alvarez, Fernando; Arena, Maria; Auteri, Domenica; Binaglia, Marco; Castoldi, Anna Federica; Chiusolo, Arianna; Colagiorgi, Angelo; Colas, Mathilde; Crivellente, Federica; De Lentdecker, Chloe; Egsmose, Mark; et al.
Abstract: The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member States, the United Kingdom (former) and France (after withdrawal of the United Kingdom from the EU), for the pesticide active substance isoflucypram. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions were reached on the basis of the evaluation of the representative use of isoflucypram as a fungicide on wheat, rye, triticale, barley and oats (field use). The reliable endpoints, appropriate for use in regulatory risk assessment, are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.